Penyelesaian Sengketa Tanah Ulayat Melalui Lembaga Adat Di Minangkabau Sumatera Barat - Alista Laquina; Devi Lateefa (LPPM Universitas Sains dan Teknologi Komputer, 2023)
Special protection efforts to deal with children who have lost their parents due to COVID-19, are carried out by the Ministry of Social Affairs by providing family-based integrative services through a program called ATENSI (Assistant to Social Rehabilitation). The ATENSI program has been going on since 2020 with the issuance of Republic of Indonesia Minister of Social Affairs Regulation Number 16 of 2020 concerning Social Rehabilitation Assistance, which was later changed to RI Social Minister Regulation Number 7 of 2021 regarding Social Rehabilitation Assistance as an effort to optimize social rehabilitation services within the Directorate General of Social Rehabilitation. ASSISTANCE is a Social Rehabilitation service with a family-, community- and/or residential-based approach through support activities for meeting the needs of a decent life, social assistance, and accessibility support.